Mangiferin mitigates neurological deficits and ferroptosis via NRF2/ARE pathway activation in cerebral ischemia-reperfusion rats - Peng, Chenjia; Zhang, Yang; Chai, Jiaqing; Zhang, Hengbo (Frontiers in Pharmacology, 2025)
IntroductionFerroptosis is a newly described form of nonapoptotic, iron-dependent cell death that plays an essential role in the pathogenesis of ischemic stroke. Targeting ferroptosis may be an effective way to treat ischemic stroke. Mangiferin (MGF) is a natural polyphenol that has been shown to protect neurological function via multiple mechanisms. However, the mechanism by which MGF inhibits ferroptosis in stroke remains unclear.MethodsAn ischemic stroke rat model was established by middle cerebral artery occlusion. Neurological scoring, TTC staining, behavioral tests, Nissl staining, HE staining and immunochemistry were used to analyze the influences of MGF on neurological deficits, the infarct area, cognitive function, neuronal morphology, histopathological injury, and the morphology of microglia and astrocytes. Transmission electron microscopy and Perls’ stain were used to evaluate the characteristics of ferroptosis. Western blotting was used to analyze the expression of NRF2, FTL, SLC7A11 and GPX4. ELISA was used to analyze the levels of cytokines, including IL-6, IL-1β and TNF-α, to evaluate neuroinflammation. Oxidative stress was evaluated by analyzing the levels of ROS, MDA, GSH, and SOD.ResultsMGF clearly improved the neurological function and learning and memory ability of stroke rats. MGF significantly decreased ROS and MDA and increased GSH, SOD. MGF significantly suppressed neuroinflammation by downregulating IL-6, IL-1β and TNF-α. Ferroptosis in stroke rats was significantly inhibited by MGF. MGF significantly increased the expression of NRF2, FTL, SLC7A11 and GPX4. The NRF2 inhibitor ML385 significantly reversed the effects of MGF on stroke rats.ConclusionMGF protects neurological function and suppresses ferroptosis via activating NRF2/ARE pathway in ischemic stroke rats.